Factors Influencing Students’ Self-Employment Intentions (SEIs): The Role of Education - Mseleku, Zethembe (African Journal of Inter/Multidisciplinary Studies, 2025)
Unemployment is a major social, political, and economic problem in the world. This problem negatively affects developed and developing economies. However, there is increasing scientific evidence that suggests most developing economies are severely affected by unemployment. While young people and adults are victims of unemployment, the body of literature suggests that unemployment is higher among the youth. Hence, the government and other relevant stakeholders are immensely challenged to explore alternative solutions to unemployment, particularly youth unemployment. One of the proposed solutions is self-employment. The practicality of self-employment is fundamentally dependent on the pursuit of intentions. This paper positions intention as the major driver towards self-employment. Grounded in the Theory of Planned Behavior (TPB), this paper analyses the factors influencing students’ self-employment intentions. In particular, the paper consolidates evidence on the extent to which level and type (general or specialised) of education influence self-employment intentions and entrepreneurial behavior among students. This study is qualitative as it relies on the corpus literature. Comprehensive literature evidence was gathered from various scholarly databases to address the purpose of this paper. The findings show that age, gender, prior entrepreneurial exposure, family, peers, personal traits, and education are factors influencing SEIs and entrepreneurial behavior among students. Specialised education is more influential on SEIs and entrepreneurial behavior than the level of education. These findings justify the need for entrepreneurship education, which can promote entrepreneurship as a solution to unemployment. Therefore, the education sector must work collaboratively with other relevant stakeholders to promote entrepreneurship education.